Pengaruh K3, lingkungan kerja dan disiplin kerja terhadap kinerja pegawai melalui motivasi sebagai variabel intervening pada suku dinas penanggulangan kebakaran dan penyelamatan Kota Administrasi Jakarta Selatan - Mattajang, Rio; Nurwulandari, Andini; Dwi Hardin, Oktafian Cahya (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this research is to analyze the effect of K3, Work Environment, and Work Discipline on Employee Performance through motivation as an intervening variable at the South Jakarta City Administration of Fire and Rescue Agency. The model was analyzed using the Structural Equation Model (SEM) using statistical software AMOS 22, SPSS, and EXCEL 2016. Data collection was carried out on the South Jakarta fire department tribe using a questionnaire, the data obtained were 100 respondents. The results obtained from this study K3, work environment, and work discipline have a positive effect on employee performance through motivation as an intervening variable. In the work environment, it is not significant (t count > 0.05) which means that it needs to be increased again to improve employee performance.